ESTUDIO DE LA INTEGRACIÓN DE ESTACIONES DE CARGA PARA VEHÍCULOS ELÉCTRICOS Y SU INFLUENCIA EN LAS REDES DE DISTRIBUCIÓN DE LA SUBESTACIÓN QUEVEDO SUR – SAN JOSÉ SUR - RENDÓN ESPINOZA, BYRON SANTIAGO (2025)
This research analyses the impact of integrating fast charging stations for electric vehicles in the San José Sur feeder, analyzing its effect on energy demand, system stability and quality of electric service